Preparation method and application of novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst

Through the preparation method of the new bismuth nanocrystalline/nitrogen-rich graphite carbon electrocatalyst, the problem of structural instability of existing catalysts during CO2 electroreduction is solved, and efficient and stable CO2 electroreduction performance is achieved, which significantly improves the selectivity and service life of the catalyst.

CN119663359AActive Publication Date: 2025-03-21CHONGQING INST OF GEOLOGY & MINERAL RESOURCES +2

Patent Information

Application Number
CN202411892352.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The existing bismuth metal-doped carbon nitride catalysts are prone to structural reconstruction such as particle size growth and active center fallout during the CO2 electroreduction process, resulting in unstable catalytic performance and increasing the difficulty of identifying active sites and controlling performance.

Method used

The preparation method of a new bismuth nanocrystal/nitrogen-rich graphite carbon electrocatalyst is adopted to form ultrafine metal bismuth nanoparticles through the chelation reaction of urea, ammonium chloride and bismuth citrate, and they are embedded in nitrogen-rich graphite carbon, forming a sandwich porous structure, and the dispersion and stability of the active components are ensured by step-by-step calcination.

Benefits of technology

It improves the electrocatalytic reduction performance and stability of the catalyst, significantly improves the selectivity and efficiency of CO2 electroreduction, extends the service life of the catalyst, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005200941680000011
    Figure HDA0005200941680000011
  • Figure HDA0005200941680000012
    Figure HDA0005200941680000012
  • Figure HDA0005200941680000021
    Figure HDA0005200941680000021
Patent Text Reader

Abstract

The invention relates to the technical field of electrocatalysis, in particular to a preparation method and application of a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, and the preparation method comprises the following steps: S1, adding urea and ammonium chloride into water, stirring, freeze-drying and grinding to obtain a chelating ligand; s2, adding bismuth citrate into the chelating ligand, and carrying out solid-phase reaction to obtain a precursor; and S3, calcining the precursor under the protection of nitrogen to obtain the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst. The problems that reduction and reconstruction reactions are likely to happen in the CO2 electrocatalytic reduction catalysis process, and the difficulty of active site recognition and performance regulation and control is increased can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a preparation method and application of a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst. Background Art

[0002] With the increasing dependence of modern society on petrochemical resources, the CO2 emission problem is no longer just an environmental issue, but has risen to the level of international relations and human survival and development. With the advancement of the dual carbon goals, many industries are looking for ways to capture and utilize carbon dioxide. At present, the conversion and utilization of CO2 are mainly achieved through electrocatalysis, photocatalysis, photoelectrocatalysis, biocatalysis and other methods. CO2 electroreduction is an efficient and environmentally friendly conversion and utilization method, that is, under the condition of applying a certain reduction potential, CO2 on the cathode surface and nearby is converted to other high-value carbon-containing compounds. CO2 is converted into various carbon-containing compounds such as CO, HCOOH, ethanol, acetic acid, propanol, propane, propionic acid, etc. through electroreduction technology. Therefore, the electrochemical reduction of CO2 to fuels and chemicals is considered to be an important way to store sustainable energy and solve climate problems, and it is also an effective means to achieve carbon neutrality.

[0003] CO2 electroreduction is mainly affected by factors such as electrode catalysts, electrolyte types and local electrode potential. Among them, the development of efficient catalysts is the key to its technology. However, the commonly used electrocatalytic materials have defects such as high cost, low activity and poor stability. Bismuth metal has high catalytic activity and selectivity in CO2 electroreduction. However, the current density and Faraday efficiency of its electrocatalytic reduction need to be further improved. At present, various methods such as crystal face exposure, morphology control, ion doping and composite have been developed to improve the electrocatalytic activity of its electrocatalysts, which has become a research hotspot in recent years.

[0004] Chinese patent CN115992365A discloses a bismuth metal-doped carbon nitride catalyst and its preparation method and application. Urea and bismuth source are used as raw materials. After mixing, freeze drying, calcination, pickling and post-treatment, a porous sheet-like bismuth metal-doped carbon nitride catalyst is obtained. However, this method still has some shortcomings: (1) The prepared bismuth metal-doped carbon nitride catalyst is composed of bismuth metal and carbon nitride, and the former is loaded on the latter. During the catalytic CO2 reduction process, structural reconstruction phenomena such as particle size growth and active center shedding are prone to occur, which cannot guarantee the stability of its catalytic performance and increases the difficulty of identifying active sites and performance regulation. (2) During the high-temperature calcination process, the atoms inside the bismuth metal nanoparticles loaded on the surface of the carbon nitride carrier will diffuse and rearrange, which will cause the nanoparticles to easily agglomerate and increase in size, thereby making the material synthesis more difficult. Summary of the invention

[0005] The present invention provides a preparation method and application of a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, which can solve the problem that reduction and reconstruction reactions are prone to occur during the catalytic CO2 electrocatalytic reduction process, which increases the difficulty of identifying active sites and regulating performance.

[0006] This application provides the following technical solutions:

[0007] A method for preparing a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, characterized in that it comprises the following steps:

[0008] S1. Add urea and ammonium chloride to water, stir evenly, and freeze-dry to obtain a chelating ligand;

[0009] S2, adding bismuth citrate to the chelating ligand, grinding, and performing a solid phase reaction to obtain a precursor;

[0010] S3. Under nitrogen protection, heat the precursor to 550° C. at a heating rate of 2 to 5° C. / min, keep warm for 2 to 3 hours, heat the precursor to 650 to 800° C. at a heating rate of 2 to 5° C. / min, keep warm for 2 to 3 hours, and cool the precursor naturally to room temperature to obtain a bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst.

[0011] The bismuth nanocrystal / nitrogen-rich graphitic carbon electrocatalyst is prepared by embedding ultrafine metal bismuth nanoparticles within nitrogen-rich graphitic carbon to form a sandwich-type porous structure.

[0012] Application of bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst in electrocatalytic reduction of carbon dioxide. The application method comprises the following steps:

[0013] 1) adding anhydrous ethanol and Nafion to the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, and dispersing them uniformly by ultrasonic treatment to obtain a suspension;

[0014] 2) evenly coating the suspension on carbon paper and drying it to obtain carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst;

[0015] 3) Using carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst as the working electrode, Ag / AgCl as the reference electrode, platinum sheet as the counter electrode, KHCO3 solution as the electrolyte solution, CO2 was introduced for electrocatalytic reduction.

[0016] Beneficial effects: In the preparation process, urea plays a chelating role, and ammonium chloride plays a role in dispersion and forming a pore structure. Urea and ammonium chloride are freeze-dried to form a uniformly mixed and highly crystallized chelate ligand. Bismuth citrate is added to the chelate ligand and ground, so that bismuth citrate and the chelate ligand can be fully coordinated and combined, and its dispersibility can be improved. This composite structure is conducive to stabilizing the bismuth ions in bismuth citrate, and limits the atomic diffusion inside the bismuth nanoparticles during the subsequent calcination process, ensuring the ultrafine particle size and uniform dispersion of the bismuth nanoparticles. The step-by-step calcination method is adopted to ensure the dispersibility and stability of the active components during the carbonization process, inhibit the agglomeration and size growth of the nanoparticles, thereby obtaining ultrafine metal bismuth nanoparticles, and embedding them in nitrogen-rich graphite carbon to form a sandwich porous structure, improve the dispersibility of the active components, increase the catalytic active sites, and thus improve the electrocatalytic reduction performance and stability of the electrode material. The bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst prepared in the present application exhibits excellent selectivity and stability in the process of electrocatalytic reduction of carbon dioxide, and can maintain efficient catalytic activity for a long time, greatly improving the catalytic efficiency compared to traditional bismuth-based catalysts.

[0017] At the same time, the preparation method of the technical solution has simple operation steps, no harmful organic solvents are needed in the preparation process, the risk of environmental pollution is reduced, and it is in line with the development concept of green chemistry. It has the advantages of strong practicality, simple process, good general applicability, etc., and has industrial application prospects. Moreover, the raw materials used in the technical solution are cheap and easy to obtain, the preparation process is simple and easy, the production cost is reduced, and the economic benefits are improved.

[0018] Furthermore, the mass ratio of urea, ammonium chloride and bismuth citrate is 10:3:0.5 to 3. Preferably, the mass ratio of urea, ammonium chloride and bismuth citrate is 10:3:1 to 2.

[0019] The mass ratio of urea, ammonium chloride and bismuth citrate ensures the effective combination of the chelating ligand and the bismuth source, and promotes the formation of uniformly dispersed ultrafine bismuth nanocrystals.

[0020] Furthermore, the grinding in step S2 is performed by ball milling at a rotation speed of 150 rpm.

[0021] Ball milling is used for dry grinding to further reduce the particle size of bismuth citrate and chelating ligand to obtain a finer and more uniform powder, which helps to form a material with high specific surface area and good dispersibility in subsequent processing and improve the performance of the final product.

[0022] Furthermore, in step S3, the product is cooled to room temperature and then ground, washed with deionized water, and vacuum dried at a temperature of 80 to 85° C. for a drying time of 2 to 2.5 hours.

[0023] After grinding, the material is washed with deionized water to ensure effective removal of impurities without introducing new pollution and keep the catalyst pure. During the drying process, the water is fully evaporated while avoiding high temperature damage to the material structure.

[0024] Further, in step 2), the carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst has a loading amount of 0.2 to 1.0 mg / cm 2 .

[0025] This loading amount not only increases the number of catalytic active sites but also avoids the increase in particle size, significantly improving the selectivity and efficiency of electrocatalytic reduction of CO2, while extending the service life of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The XRD diagrams of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts prepared in Examples 1, 2 and 3 of the present invention.

[0027] Figure 2 FT-IR images of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts prepared in Examples 1, 2 and 3 of the present invention.

[0028] Figure 3 This is a SEM image of the metallic bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1 of the present invention.

[0029] Figure 4 This is a TEM image of the metallic bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1 of the present invention.

[0030] Figure 5 This is the HRTEM image of the metallic bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1 of the present invention.

[0031] Figure 6 These are the SEM and HRTEM images of the bismuth / carbon electrocatalyst prepared in Comparative Example 1.

[0032] Figure 7 This is the X-ray diffraction pattern of the electrocatalyst prepared in Comparative Example 2.

[0033] Figure 8 It is the Faraday efficiency of the electrocatalytic CO2 electroreduction reaction to produce formic acid in Examples 1, 2, 3 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0034] The following is further described in detail through specific implementation methods:

[0035] Example 1

[0036] A method for preparing a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst comprises the following steps:

[0037] Step S1, adding 10g urea and 3g ammonium chloride into 100ml deionized water, stirring magnetically for 2h, placing it in a freeze dryer for freeze drying to obtain a loose powder solid, and grinding it evenly to obtain a chelating ligand.

[0038] Step S2, adding 0.5 g of bismuth citrate to the chelated ligand of step S1, placing it in a ball mill for ball milling at a speed of 150 rpm, and performing a solid phase reaction to obtain a precursor.

[0039] Step S3, placing the precursor obtained in step S2 into a tubular furnace, using nitrogen as a protective gas, heating from room temperature to 550°C at a heating rate of 2°C / min, keeping warm for 2h, then heating to 800°C at a heating rate of 5°C / min, keeping warm for 2h, and naturally cooling to room temperature to obtain a black powder sample.

[0040] Step S4, grinding the black powder sample obtained in step S3 evenly, washing it with deionized water to remove impurities, and drying it in a vacuum drying oven at 80° C. for 2 h to obtain a bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst.

[0041] Step S5, application of bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst in electrocatalytic reduction of carbon dioxide, the application method comprising the following steps:

[0042] 1) Weighing bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst, adding anhydrous ethanol and Nafion to the bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst, the mass ratio of bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst, anhydrous ethanol and Nafion solution is 0.5-2:950:50, preferably 0.5:950:50, ultrasonically treating for 1 hour to obtain a uniformly dispersed suspension.

[0043] 2) The suspension was evenly coated on the carbon paper and dried in an oven at 60°C to obtain carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst. The loading amount of the electrocatalyst was controlled by adjusting the amount of the suspension, and the loading amount of the electrocatalyst was 0.2 mg / cm 2 .

[0044] 3) An H-type electrolytic cell was used, with carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst as the working electrode, Ag / AgCl as the reference electrode, and platinum sheet as the counter electrode. The volume of the cathode chamber and the anode chamber were 100 ml respectively, and 50 ml of 0.5 M KHCO3 solution was added to each electrolytic chamber as the electrolyte solution, separated by a Nafion membrane (proton exchange membrane Nafion117). After setting the electrode potential, the reaction temperature was set at 20 ml min -1CO2 was introduced into the electrolyte in the cathode chamber at a flow rate of , and the reactor was started. After the reaction was completed, the liquid phase product in the electrolyte was analyzed by nuclear magnetic resonance spectrometer, and the gas phase product was analyzed by gas chromatography.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that the amount of bismuth citrate added in step S2 is 1 g, and bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst is obtained.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that the amount of bismuth citrate added in step S2 is 2 g, and bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst is obtained.

[0049] Comparative Example 1

[0050] The difference between this comparative example and Example 1 is that no chelating ligand is added, and the bismuth citrate is ball-milled, calcined under nitrogen protection, and cooled to obtain a bismuth / carbon electrocatalyst.

[0051] Comparative Example 2

[0052] The difference between this comparative example and Example 1 is that during the calcination process, under nitrogen protection, the temperature is raised from room temperature to the pyrolysis temperature at a heating rate of 2°C / min, from room temperature to 550°C, kept warm for 2h, and naturally cooled to room temperature to obtain an electrocatalyst.

[0053] The electrocatalysts prepared in Examples 1-3 and Comparative Examples 1 and 2 were measured, and the results were as follows:

[0054] 1. Figure 1 The XRD pattern of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1-3 is shown in FIG. Figure 1 It can be seen that the main diffraction peaks of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts prepared in Examples 1-3 match the diffraction peaks of rhombic hexahedral metal bismuth, and no obvious diffraction peaks of bismuth oxide are found, confirming that the bismuth element exists in the form of metallic bismuth and has good crystallinity. Obvious graphite carbon diffraction peaks also appear. No other miscellaneous peaks are found, indicating that the purity of the sample is high. Therefore, it can be determined that the electrocatalysts prepared in Examples 1-3 are mainly composed of metallic bismuth and graphite carbon.

[0055] 2. Figure 2 FT-IR images of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts prepared in Examples 1-3. Figure 2 It can be seen that the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts prepared in Examples 1-3 contain a large number of carbon-containing groups.

[0056] 3. Figure 3This is a SEM image of the metal bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1. Figure 3 It can be seen that the metallic bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1 is composed of ultrathin nanosheets with obvious wrinkles. The thickness of the sheet layer is very thin, significantly less than 10 nanometers, and no obvious particles are found, indicating that the metallic bismuth is highly dispersed in the ultrathin nanosheets.

[0057] 4. Figure 4 TEM image of the metal bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1. Figure 4 It can be seen that the metal bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1 presents an ultra-thin flake structure without obvious metal bismuth particles.

[0058] 5. Figure 5 HRTEM image of the metal bismuth / nitrogen-rich graphite carbon electrocatalyst prepared in Example 1. Figure 5 It can be further observed that the surface of the metal bismuth / nitrogen-rich graphite carbon electrocatalyst has a certain degree of lattice fringes, confirming the formation of graphite carbon, and no obvious metal bismuth particles are found. Therefore, it can be known that the formed metal bismuth is highly embedded in the nitrogen-rich graphite carbon, forming a sandwich porous structure.

[0059] 6. Figure 6 The SEM of the bismuth / carbon electrocatalyst prepared in Comparative Example 1 ( Figure 6 (a)) and HRTEM images ( Figure 6 (b)). Figure 6 As can be seen from (a), the bismuth / carbon electrocatalyst prepared in Comparative Example 1 is composed of thinner sheet stacks, with a large number of stacked pore structures, and a large number of metallic bismuth nanoparticles are found. Figure 6 As can be seen from (b), the bismuth / carbon electrocatalyst prepared in Comparative Example 1 is composed of a large number of metal bismuth nanoparticles. Therefore, it can be seen that when the chelating agent is not introduced, the sample formed belongs to the metal bismuth nanoparticles loaded on the surface of the carbon material, and the formed metal bismuth particles have a larger particle size.

[0060] 7. Figure 7 is the X-ray diffraction pattern of the electrocatalyst prepared in Comparative Example 2. Figure 7 It can be seen that the electrocatalyst prepared in Comparative Example 2 has the following 0 Strong diffraction peaks appeared, corresponding to the (0 1 2), (0 1 4), (1 1 0) and (2 0 2) crystal planes of rhombic hexahedral bismuth. In addition, at 30.1, and 32.6 0The diffraction peaks of match those of Bi2O3 (2 22) and (3 2 1). It can be seen that the electrocatalyst prepared in Comparative Example 2 is a mixture of metallic bismuth and Bi2O3. It can be seen that the calcination process has an important influence on the structure of the prepared electrocatalyst.

[0061] 8. Figure 8 The Faraday efficiency of the electrocatalytic CO2 electroreduction reaction to produce formic acid in Examples 1-3 and Comparative Examples 1 and 2. Figure 8 It can be seen that under the same reaction conditions, the Faraday efficiency of formate production in Example 1 is 83.7%, the Faraday efficiency of formate production in Example 2 is 89.6%, and the Faraday efficiency of formate production in Example 3 is 95.2%. The Faraday efficiency of formic acid production in Comparative Example 1 is 61.2%, and the Faraday efficiency of formic acid production in Comparative Example 2 is 26.5%. It can be seen that the catalytic performance of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalysts of Examples 1-3 is significantly higher than that of Comparative Examples 1 and 2. It is thus confirmed that the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst of the present invention has excellent catalytic performance because ultrafine metal bismuth nanoparticles are embedded in ultrathin nanosheets of nitrogen-rich graphite carbon to form a sandwich structure, which effectively improves the dispersibility of the active components and increases the catalytic active sites.

[0062] The above are only embodiments of the present invention. The invention is not limited to the field involved in this implementation case. The common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several deformations and improvements can be made without departing from the structure of the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of its claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a novel bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, characterized in that: The steps include: S1. Add urea and ammonium chloride to water, stir evenly, and freeze-dry to obtain a chelating ligand; S2, adding bismuth citrate to the chelating ligand, grinding, and performing a solid phase reaction to obtain a precursor; S3. Under nitrogen protection, heat the precursor to 550° C. at a heating rate of 2 to 5° C. / min, keep warm for 2 to 3 hours, heat the precursor to 650 to 800° C. at a heating rate of 2 to 5° C. / min, keep warm for 2 to 3 hours, and cool the precursor naturally to room temperature to obtain a bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the urea, ammonium chloride and bismuth citrate is 10:3:0.5-3.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the urea, ammonium chloride and bismuth citrate is 10:3:1-2.

4. The preparation method according to claim 1, characterized in that: The grinding in step S2 is performed by ball milling at a rotation speed of 150 rpm.

5. The preparation method according to claim 1, characterized in that: Step S3: After cooling to room temperature, grinding is performed, washing is performed with deionized water, and vacuum drying is performed at a drying temperature of 80 to 85° C. and a drying time of 2 to 2.5 hours.

6. Bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst prepared by the preparation method according to any one of claims 1 to 5.

7. The bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst according to claim 6, characterized in that: Ultrafine metallic bismuth nanoparticles are embedded in nitrogen-rich graphitic carbon to form a sandwich-type porous structure.

8. Use of the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst according to claim 6 or 7 in the electrocatalytic reduction of carbon dioxide.

9. The use according to claim 8, characterized in that: The application method includes the following steps: 1) adding anhydrous ethanol and Nafion to the bismuth nanocrystal / nitrogen-rich graphite carbon electrocatalyst, and dispersing them uniformly by ultrasonic treatment to obtain a suspension; 2) evenly coating the suspension on carbon paper and drying it to obtain carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst; 3) Using carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst as the working electrode, Ag / AgCl as the reference electrode, platinum sheet as the counter electrode, KHCO3 solution as the electrolyte solution, CO2 was introduced for electrocatalytic reduction.

10. The use according to claim 9, characterized in that: Step 2) The carbon paper loaded with bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst, the loading amount of bismuth nanocrystals / nitrogen-rich graphite carbon electrocatalyst is 0.2-1.0 mg / cm 2 .

Citation Information

Patent Citations

  • Graphite-phase carbon nitride photocatalyst modified by basic bismuth carbonate and preparation method of graphite-phase carbon nitride photocatalyst

    CN108339561A

  • Bismuth metal doped carbon nitride catalyst as well as preparation method and application thereof

    CN115992365A

  • Multilayer nitrogen-doped carbon-coated bismuth material as well as preparation method and application thereof

    CN116111063A

Cited By

  • Graphite / bismuth nanosheet electrocatalytic anode material as well as preparation method and application thereof

    CN120714611A